ATTENUATION OF HEAVY METALS IN SEDIMENTS OF THE BONNY ESTUARY, NIGERIA: THE ROLE OF OXYGEN - Ogbuagu, Dr. Dike Henry; Dinney, Dagogo Eras (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Sediments of the Bonny Estuary, which is repository to pollutants from various industrial and shipment activities in its catchment was investigated for rate of natural attenuation of toxic metals (Cd, Mn, Cr, Pb, Cu, Ni, Fe) under aerobic and anaerobic conditions. Samples were collected with pre-grab sampler from seabed, sieved in the laboratory and monitored under aerobic and anaerobic conditions. After incubation at 18Â°C, harvests were made on days 1, 14, 28 and 42 and levels of the metals determined spectrophotometrically. Variation plots, ANOVA, Means plots, Studentâ€™s t-test and Pearson correlation (r) were used to analyze data. Concentration reductions were higher in aerobic condition in the order Cu(15.5%)> Cd(11.4%)> Fe(8.0%)>Mn(5.7%)> Cr(4.4%)> Ni(4.2%)>Pb(3.9%) than in anaerobic condition which was in the order Cu(7.5%)> Cd(7.4%)>Pb(2.4%)>Mn/Cr(1.8% each)> Fe(0.9%)> Ni(0.5%). There was significant heterogeneity in metals reductions (Sig. F=0.000) on all the harvest days, especially of Cu, Pb and Fe at P<0.05. Attenuation of Mn also differed markedly between the aerobic and anaerobic conditions (Sig. t=0.005) at the 95% confidence interval. pH influenced the attenuation of Ni (r=0.766) and Fe (r=0.795) (P<0.05) as well as Cd (r=0.968), Cr (r=0.861), Pb (r=0.989) and Cu (r=0.950) (P<0.01). Results indicate that rate of attenuation was slow and slightly enhanced by oxygenation.